Effect of Mental Imagery Coupled with Plyometric on Vertical Jump and Agility - Taneja, Kanika; Zutshi, Kalpana; Ram, CS; Solanki, Anuradha (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2019)
Background: Among the extensive research done, there are many studies on imagery use by athletes. These studies have looked at athletes imagery use under a number of different conditions except its use clubbed with physical training which has less available evidences.1,29,35The additional advantage being in the case of acute injuries, when actual training is not possible, imagery training is believed to be extremely beneficial without causing any further exertion to the injury.The objective of the study is to study the efficacy of a program combining mental and physical practice with the efficacy of a program composed of only plyometric training or only mental practice on vertical jump and Agility.Methods: A total of 36 healthy male volunteers participated in the study from Hamdard University and Darbari Lal D.A.V. Model School. It was a different subject experimental study with a Pre-Test – Post Test design. They were randomly assigned between three groups. Main outcome measure was vertical jump using Stand and reach test and Agility t-test for Agility.The data was analyzed with the help of statistician using SPSS 15.0 version.Paired-t test was used to see the within Group analysis of both the outcome measures as vertical jump and Agility t-test. Results of training from pretesting to post testing were analyzed using a one-way ANOVA and compared across three groups. When a significant F-ratio was found, a Bonferoni’s post-hoc test was used to determine differences between mean values across the three groups. Alpha was set at .05 to achieve statistical significance for all analysis.Results: It was seen that all the three groups i.e. combination (plyometric and mental imagery) group C, mental imagery training (group B) and plyometric training (group A) has yielded significant improvements on both the outcome after training for 6 weeks. Combined training significantly improved performance in agility test and vertical jump as compared to plyometric and imagery alone(p-value=0.000 for difference VJ and p-value=0.000 for difference test at p 5% significance).Conclusion: It was concluded through the study that combination of mental imagery training with plyometric yields better and added effects than the intervention involving plyometric and mental imagery training alone.